The Reception of Dionysius up to Maximus the Confessor - Louth, Andrew (Modern theology, 2008)
There are various odd features about the initial reception of the Corpus Dionysiacum in the sixth century. The reception was, at first, slow and mainly concerned the few, controversial Christological assertions of the CD. The influence of the CD was mediated through a single edition, complete with introduction, variant readings, and scholia, all furnished by John of Scythopolis. The initial reception of the CD in the Syriac world seems very different: independent (at least to begin with) of Scythopolis’ edition, and deeply Origenistic. Yet, in other ways, the CD reflects the kind of historical interests we find elsewhere in the sixth century.